Reducing mechanical anisotropy by formation of symmetrical ring-like texture via final-pass heavy reduction rolling in Mg alloy - B.Q. Shi; R.D. Zhang; X.L. Shang; Y.Z. Wang; T. Long; J.M. Jiang; C.Q. Li; B.Y. Liu (Journal of Materials Research and Technology, 2023)
The traditionally used low-reduction rolling (LRR) always causes a ‘TD-split’ texture (TD: transverse direction) in Mg–Zn–RE alloy plates, which results in planar anisotropy in the mechanical properties and limited formability. Therefore, it is necessary to modify such texture to reduce mechanical anisotropy and increase formability. In the present work, a unidirectional rolling approach, final-pass heavy reduction rolling (FHRR), was applied to a Mg–1Zn–1Y–0.5Zr alloy ingot which have exhibited ‘TD-split’ texture using LRR. It was found that, when the reduction ratio of the final-pass rolling is above 50% and combined by suitable annealing, a symmetrical ring-like texture formed, where the basal poles tilted by about 50° from normal direction (ND) towards both of TD and rolling direction (RD). The rolled plates exhibited an obviously reduced mechanical anisotropy: the ratio of yield strength along RD and TD (RYSR/T) was of 1.13–1.17, much lower than that of the plates with ‘TD-split’ texture upon FHRR of 30% and annealing (RYSR/T: 1.34). To reveal the formation mechanism of such texture, the microstructure and texture evolution during rolling and annealing was thus investigated and much attention was paid on the role of the final-pass reduction. Besides, the effect of as-annealed texture on the planar anisotropy in mechanical properties was investigated and discussed in terms of its association with the activities of different deformation mechanisms.